O Wildze Stefana Żeromskiego - Obsulewicz, Beata K. (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
This article is about a short story entitled Wilga (The Oriole) (1925). This work was written shortly before the writer’s death and is his elegiac farewell to his home in Konstancin, an expression of love to his daughter Monica and a kind of his literary summary and a testament. An important part of the discussion is focused on how the writer used his own autobiography in his artistic works and how he is relying on his memory while creating the literary image. This article also focuses on ornithological knowledge of the writer which is an important fact that has not been given enough attention in relation to Żeromski’s works. It was reconstructed on the basis of his Diaries, Memoirs and literary works. The presented findings can serve as an aid in developing a monograph on the birds themes in the works of the author of The Labors of Sisyphus.